Research trends and clinical evidence: A comparison of surgical vs. conservative approaches for chronic pelvic pain syndrome – a systematic review and bibliometric analysis - Saputra, I Gede Agus Rio; Pramana, Anak Agung Ngurah Gede Anggra; Marta, Kadek Fajar (Institute of Computer Science (IOCS), 2025)
Chronic Pelvic Pain Syndrome (CPPS) is a complex medical condition that affects patients' physical, emotional, and social quality of life. Its management involves two main approaches: surgical and conservative. However, there are significant differences in the effectiveness, risks, and long-term impacts of each approach. This study aims to evaluate the effectiveness of surgical and conservative approaches in managing CPPS through a systematic review and bibliometric analysis, focusing on pain reduction, improvement in quality of life, and risk of complications. This research employs the Systematic Literature Review (SLR) method, following the PRISMA guidelines to search, screen, and evaluate relevant literature from databases such as PubMed, Scopus, and the Cochrane Library. The quality of the relevant studies is assessed using standardized appraisal tools. Quantitative data are analyzed through bibliometric analysis to identify differences in effectiveness between surgical and conservative approaches. The results indicate that the surgical approach is more effective in reducing severe and refractory pain compared to conservative therapy, but it is associated with a higher risk of complications. Conversely, the conservative approach provides benefits for mild to moderate symptoms with minimal risk and lower cost. In the context of Indonesia, the conservative approach is more suitable to be implemented as the first-line treatment for CPPS, with surgical options considered for cases that do not respond to initial therapy.